1994
DOI: 10.1002/ajpa.1330930410
|View full text |Cite
|
Sign up to set email alerts
|

Maximum length of the tibia: How did Trotter measure it?

Abstract: For over forty years, Trotter and Gleser's (1952) stature estimation formulae have provided what was thought to be a consistent and reliable means to estimate stature from long bone measurements. The 1952 formulae for white and black males were based on World War I1 casualties, and for white and black females on the Terry collection. The formulae were reevaluated using Korean War dead (Trotter and Gleser, 1958). The 1958 study afforded larger samples and permitted inclusion of a Mexican and a mixed Mongoloid s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
1
3

Year Published

1996
1996
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 3 publications
2
35
1
3
Order By: Relevance
“…In a few cases ( N = 14), sex was determined from measurements where mean values for each sex had been determined from discriminatory analysis of osteometrics from postcranial elements derived from morphologically sexed adult skeletons. Living stature was estimated using the regression equations of Trotter and Gleser (1952, 1958), excluding the tibiae for female equations (see Jantz et al,1994), and the bone chosen for assignment of stature in each individual skeleton was chosen in order of best correlation to the results given from the left femur.…”
Section: Methodsmentioning
confidence: 99%
“…In a few cases ( N = 14), sex was determined from measurements where mean values for each sex had been determined from discriminatory analysis of osteometrics from postcranial elements derived from morphologically sexed adult skeletons. Living stature was estimated using the regression equations of Trotter and Gleser (1952, 1958), excluding the tibiae for female equations (see Jantz et al,1994), and the bone chosen for assignment of stature in each individual skeleton was chosen in order of best correlation to the results given from the left femur.…”
Section: Methodsmentioning
confidence: 99%
“…Researchers believed quantitative examinations employed unbiased procedures because they dealt with numerical values; visual assessment was subject to judgment errors by the researcher attempting a specific technique. However, similar issues arose in metric studies of long bones, as exemplified by the prediction errors made with certain contemporary "canonical" formulae for tibia research (Jantz et al, 1994). This indicates quantitative methods 2 were and continue to be more subjective than once thought.…”
Section: )mentioning
confidence: 95%
“…However, there are different regression formulae obtained from different skeletal samples (Manouvrier, 1893;Pearson, 1899;Olivier and Tissier, 1975;Gleser, 1952, 1958;Sciulli et al, 1990;Sciulli and Giesen, 1993;Feldesman and Fountain, 1996;among others), and some of these methods yield more accurate figures than others. For instance, by comparing different methods with anatomical data, Formicola (1993) and Formicola and Franceschi (1996) concluded that Pearson (1899) and Olivier et al (1978) use formulae which are better stature estimators than those from Trotter and Gleser (1952), whose estimating formula show inconsistencies in the measurement techniques used for the tibia sample (Jantz, 1992;Jantz et al, 1994). Also, regression equations have usually been obtained from living populations and thus it is debatable whether a given prehistoric sample can be comparable from a genetic and environmental point of view to those populations.…”
Section: Methodsmentioning
confidence: 99%